Obtenção de nanopartículas de própolis encapsulado em quitosana com ação biocida para modificação de filtros de ar - Pereira, Jéssica Claro (2023)
Atmospheric air pollution represents increasingly harmful risks to public health and the environment. Attached to this problem, the coronavirus pandemic has brought several new challenges to our health system. Air conditioner filters are the first physical barrier between the external and indoor rooms, and, in addition to retaining pollutants and bioaerosols, it is important that the proliferation of retained microorganisms is inhibited, in order to prevent these filters from becoming a secondary source of contamination. Therefore, the present work had as objectives the synthesis of chitosan-propolis nanoparticles, and their impregnation in a commercial filter, attributing it a biocidal effect. Chitosan and propolis formulations were studied based on ideal physicalchemical parameters, and the nanoparticles were synthesized by ionic gelation method. Physical properties such as particle size, zeta potential, encapsulation efficiency, FTIR spectroscopy were investigated, as well as particle morphology. Two nanoparticle formulations were pre-selected, showing the best ratios between sizes (392nm e 457nm) and encapsulation efficiencies (78% e 75%), and the chemical analysis confirmed the propolis incorporation into the chitosan matrix. The nanoparticles showed antimicrobial action against S. aureus, with 97% inhibition, and, at least in the concentrations of nanoparticles evaluated, they didn’t show activity against the E. coli strain. Filtration efficiency, permeability, and filter quality factor were analyzed before and after nanoparticle’s impregnation, and their presence didn’t affect its final quality. Thereby, it was verified that these work results were promising for the manufacture of chitosan-propolis nanoparticles for later incorporation into functional matrices, in a sustainable way, in order to reduce the contamination of pathogens in the most diverse environments.